ANALISIS MODEL PENDAPATAN DAN STRATEGI MONETISASI DIGITAL PADA PLATFORM E-COMMERCE - Anisa Maya Sufa; Zahfira Halim; Nabila Asyifa Zaini; Pebrian Syahputra Sinulingga; Nurbaiti (Jurnal Ekonomi Bisnis Manajemen dan Akuntansi (JEBISMA), 2025)
The growth of the digital economy in Indonesia has driven the rapid development of e-commerce platforms such as Shopee, which is a prime example of the transformation of digital-based business models. This study aims to analyze revenue models and digital monetization strategies on e-commerce platforms in Indonesia and their relationship to business sustainability. The method used is qualitative research with a library research approach, through a review of literature from various academic sources and reliable journals. The results of the analysis show that e-commerce revenue models in Indonesia generally consist of six main types, namely advertising revenue, sales, subscriptions, freemium, transaction fees, and affiliations. Shopee, as a case study, implements a combination of these models through transaction commissions, paid advertising, delivery services, and financial features such as ShopeePayLater. Effective digital monetization strategies depend on the use of technology, data analytics, user personalization, and cross-sector collaboration. The integration of diversified revenue models and appropriate digital monetization strategies has been proven to increase the stability and sustainability of e-commerce businesses amid fierce digital market competition.